2021
DOI: 10.3390/su13073748
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on the NASDAQ’s Potential for Sustainable Investment Practices during the Financial Shock from COVID-19

Abstract: There is a growing demand for sustainable business practices and for sustainable and impact investment as has been signaled by the Sustainable Development Goals ratified by all the United Nations members. However, there is not that much evidence on how sustainable investments perform during crises compared to regular investments. This paper investigates if sustainable investments within the NASDAQ have a lower volatility rate when reacting to a significant global crisis such as the COVID-19 pandemic. It groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…In this context, the notion of sustainable development represented an extremely revealing vision of the interest and willingness of nations and their governments to adopt viable modes of production and consumption and invent and promote development compatible with nature as a vehicle for favouring present and future social equity (Shields, Ajour & Vila, 2021). Thus, sustainable development refers to development that produces a reasonable and stable profitability over time, respects the cultural and ethical values of the communities involved and maintains the fundamental characteristics of the natural system over time in terms of its components and interactions (Miranda et al, 2007;Ajour, Consolación-Segura & Huertas-García, 2020).…”
Section: Governmental and Citizen Responsibilitymentioning
confidence: 99%
“…In this context, the notion of sustainable development represented an extremely revealing vision of the interest and willingness of nations and their governments to adopt viable modes of production and consumption and invent and promote development compatible with nature as a vehicle for favouring present and future social equity (Shields, Ajour & Vila, 2021). Thus, sustainable development refers to development that produces a reasonable and stable profitability over time, respects the cultural and ethical values of the communities involved and maintains the fundamental characteristics of the natural system over time in terms of its components and interactions (Miranda et al, 2007;Ajour, Consolación-Segura & Huertas-García, 2020).…”
Section: Governmental and Citizen Responsibilitymentioning
confidence: 99%
“…As technology has advanced, media news has become an important signal that captures the nonlinear factors that influence stock price performance, thereby improving the accuracy of stock price forecasting. Recent studies have suggested that media news and related sentiments can influence corporate and investor behavior as well as stock market performance [8]. Similarly, stock market trends are influenced by various events such as political influences, information security events [9,10], specific news or announcements [2], and national politics [11].…”
Section: Introductionmentioning
confidence: 99%
“…For the COVID-19 period, markets valued firms lower when they were more exposed to international trade, higher corporate debt, and lower cash holdings [24]. Shields, El Zein, and Brunet [25] show that sustainable stocks have lower volatility than less sustainable stocks during the COVID-19 period using a GARCH framework. In addition, socially responsible and sustainable stocks measured by environmental, social, and governance criteria (ESG) have turned out to provide more resilience during the GFC [26] and the COVID-19 shock [27,28].…”
Section: Introductionmentioning
confidence: 99%